(3QSGdI aj GdcjejGA hGdCMLGQ GdcQjeIs
(3ChdgG (B:s
(3LGA ajgG HYO GdHSedI (B" (3JOGHjQ heHGbd ddMLQ QCjJgG ai fSNI TjN Jbi hfbdJgG ceG ajgG (B" (3GYde Cf GdMLQ bQjH ef eYOf GdPgH s
(3BNQgG (B:s
(3hHYO Pdc JCNP ChbjI ef GdMLQ hCQHY ChQGb ef GdeGA jZdi ajg MJi jPgH GdeGA Ke Edi JeGe GdYed hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B6 - (3U(B7s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B57 s
Keywords: (3GdcjejGA h GdWHjYjGJs